Here be dragons - rule 1 in managing a technology start-up beware the easy money. - Coetzee, F.M (IEEE spectrum)
This article highlights the basic problems in starting a tech company, in particular those that set the business and technical sides at each other's throats. Most business plans concentrate on potential customers, pricing models, and marketing projections, with technical development dealt with in a few paragraphs and budget line items. A true development plan, by contrast, fully describes the functionality of different product versions, as well as resources, risks, and timelines. Also, taking money puts a value on the company. Taking money carelessly may deliver a tax of overvalued stock and unaffordable options. In short, the wrong first funding can destroy your company. The only way to avoid this pitfall is to do careful planning with your own independent advisors and lawyers.